Menentukan Kepuasan Masyarakat dalam Membuat Surat Izin Mendirikan Bangunan pada Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu menggunakan Algoritma K-Nearest Neighbor - Hutasoit, Rahel Adelina; Suhada, Suhada; Irawan, Eka; Damanik, Irfan Sudahri; Susiani, Susiani (MEANS (Media Informasi Analisa dan Sistem), 2020)
This research aims to classify the public satisfaction on the creation of building permits in the Office of Investment and integrated service of one door Pematangsiantar. Data is obtained from the results of a community questionnaire from 2019, with a sample of 80 data in society. The attributes used as many as 9, namely terms, procedures, service time, cost/tariff, service products, implementing competence, implementing conduct, infrastructure and handling complaints. The method used in this research is the K-Nearest Neighbor (KNN) algorithm and was processed using the RapidMiner Studio 8.1 software to determine the public satisfaction of the creation of building permits. The data used is divided into two, which are training data used 50 data and data testing used as much as 30 data. With this research is expected to help the Department of Investment and Integrated services one door Pematangsiantar to evaluate the service system provided to the public to meet the expectations of the community in the manufacture of building permits.